Effectiveness assessment of protected areas based on the states, trends, and relative changes in forest ecosystem: a case study in the Three Parallel Rivers Region, China - Shen, Hua; Feng, Chunting; Tian, Jing; Fan, Luqiong; Cao, Ming; Wang, Wei (Frontiers in Ecology and Evolution, 2024)
Establishing protected areas (PAs) is a major measure of biodiversity conservation, and various methods have been explored to assess PAs' effectiveness. However, those methods mainly compared the relative changes in land cover between treated samples inside the PAs and their matched samples outside the PAs, which would produce misjudgments, especially in some climax communities with a relatively steady state.Thus, in this study, we constructed an integrated framework through a series of assessments according to the state, trend, and relative change of each PA to explore the conservation effectiveness of PAs in the Three Parallel Rivers Region in China from 2000 to 2020. Here, "state" refers to the difference among samples from within and outside the PA, assessed through yearly sample mean comparison. "Trend" means linear regression of mean forest area of each PA throughout the assessment period. "Relative change" means the difference in the mean value of the slope of forest changes between the treated samples inside each PA and their matched control samples outside of PAs.The entire forest area within all PAs in the Three Parallel Rivers Region showed a significant increasing trend from 2000 to 2020 (R 2 =0.919, P<0.05). Among all the PAs, twelve (86%) had a positive effect on protecting the forest ecosystem, and two had a